On the Meanings of Self‐Regulation: Digital Humanities in Service of Conceptual Clarity. Issue 5 (31st July 2015) - Burman, Jeremy T.; Green, Christopher D.; Shanker, Stuart
<x xml:space="preserve">Abstract</x> Self‐regulation is of interest both to psychologists and to teachers. But what the word means is unclear. To define it precisely, two studies examined the American Psychological Association's system of controlled vocabulary—specifically, the 447 associated terms it presents—and used techniques from the Digital Humanities to identify 88 closely related concepts and six broad conceptual clusters. The resulting analyses show how similar ideas are interrelated: self‐control, self‐management, self‐observation, learning, social behavior, and the personality constructs related to self‐monitoring. A full‐color network map locates these concepts and clusters relative to each other. It also highlights some of the interests of different audiences, which can be described heuristically using two axes that have been labeled abstract versus practical and self‐oriented versus other‐oriented.